2000
DOI: 10.1016/s0927-6505(99)00126-7
|View full text |Cite
|
Sign up to set email alerts
|

On the optimum spacing of stereoscopic imaging atmospheric Cherenkov telescopes

Abstract: For stereoscopic systems of imaging atmospheric Cherenkov telescopes (IACTs), a key parameter to optimize the sensitivity for VHE γ-ray point sources is the intertelescope spacing. Using pairs of telescopes of the HEGRA IACT system, the sensitivity of two-telescope stereo IACT systems is studied as a function of the telescope spacing, ranging from 70 m to 140 m. Data taken during the 1997 outburst of Mrk 501 are used to evaluate both the detection rates before cuts, and the sensitivity for weak signals after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…We studied the basic design parameters for the next three telescopes using the Monte Carlo technique. Similar studies have been carried out previously, for example by the VERITAS [3] and HESS [4] groups. We started from optimized parameters obtained by a previous study and our experience with CANGAROO-I, [1] and verified those results.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We studied the basic design parameters for the next three telescopes using the Monte Carlo technique. Similar studies have been carried out previously, for example by the VERITAS [3] and HESS [4] groups. We started from optimized parameters obtained by a previous study and our experience with CANGAROO-I, [1] and verified those results.…”
Section: Introductionsupporting
confidence: 69%
“…With a likelihood analysis and the above-mentioned camera design ("setup-2"), we proceeded to design a stereoscopic telescope system. Previous studies have investigated the effect of the telescope spacing [3] [4]. These indicated that a spacing within a range of 80 to 120 m is best.…”
Section: Stereo Modementioning
confidence: 99%
“…[20]). Considered as a function of one telescope depending on the impact parameter of observation 4 , the fluctuations L of the number of photoelectrons detected by a telescope are directly related to the energy resolution (e.g. [20]).…”
Section: Problem Formulationmentioning
confidence: 99%
“…Thus their optimization has been figured out by finding via Monte Carlo simulations the best spacing among them in regular and symmetrical geometries and by optimizing the individual parameters of the telescopes (e.g. [4,5]). The spacing among the telescopes represents a trade-off between a good stereoscopic view of the showers and the requirement of a large effective area for good sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation